FACTORS AFFECTING THE UNDERSTANDING OF UMKM IN PREPARING FINANCIAL REPORTS ACCORDING TO SAK EMKM IN GUNUNG ANYAR SUB-DISTRICT - Agung Budi Wicaksono; Tituk Diah Widajantie (Yayasan Education and Social Center, 2023)
Preparation of accurate and timely financial statements is very important for MSMEs to be able to monitor financial performance and make good business decisions. However, MSMEs often experience difficulties in preparing financial statements in accordance with Financial Accounting Standards for Micro, Small and Medium Entities. Some factors that can affect the understanding of MSMEs in preparing financial statements according to Sak EMKM are information and socialization, educational background, education level, business size, length of business. So this study aims to test and prove the factors that affect the understanding of micro, small and medium enterprises in the preparation of financial statements based on accounting standards for micro, small and medium entities in MSMEs in Gunung Anyar district. The type of research used in this study is quantitative research. The data analysis technique used in this study uses Partial Least Square (PLS) which consists of outer model and inner model. The results showed that Information and Socialization, Educational Background, Education Level did not have a significant effect on the understanding of MSME actors in preparing financial statements based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). Meanwhile, Business Duration and Business Size have a significant effect on the understanding of MSME actors in preparing financial statements based on SAK EMKM in Gunung Anyar district.